2020
DOI: 10.3390/antiox9100977
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Geraniol on Oxidative, Inflammatory and Apoptotic Alterations in Isoproterenol-Induced Cardiotoxicity: Role of the Keap1/Nrf2/HO-1 and PI3K/Akt/mTOR Pathways

Abstract: Background: Myocardial infarction (MI) is still a major contributor to mortality worldwide, and therefore, searching for new drugs is an urgent priority. Natural products are a renewable source for medicinally and pharmacologically active molecules. The objective of this study was to explore the potential of geraniol, a monoterpene alcohol, to protect against MI. Methods: Five groups of Wister rats were used: a control group; a group treated only with geraniol; a group treated only with isoproterenol, to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…For example, geraniol and levosimendan regulate autophagy to reduce oxidative stress and limit the inflammation cascade through PI3K/Akt/mTOR. Because levosimendan can inhibit aggregation, it is more suitable for hypercoagulation and hyperlipidemia ( Tawfik et al, 2018 ; Younis et al, 2020 ).…”
Section: Pi3k-targeted Therapy In Atherosclerosismentioning
confidence: 99%
“…For example, geraniol and levosimendan regulate autophagy to reduce oxidative stress and limit the inflammation cascade through PI3K/Akt/mTOR. Because levosimendan can inhibit aggregation, it is more suitable for hypercoagulation and hyperlipidemia ( Tawfik et al, 2018 ; Younis et al, 2020 ).…”
Section: Pi3k-targeted Therapy In Atherosclerosismentioning
confidence: 99%
“…Oxidative stress leads to the activation of reactive oxygen species which as a result amplifies the pathogenesis of neuropathic pain [ 21 , 22 , 23 ]. It has been reported that the underlying cause of oxidative stress-mediated neuropathic pain is the under-expression of Nrf2 [ 24 , 25 , 26 ], a transcription factor involved in the regulation of genes that encodes antioxidant proteins and phase 2 detoxifying enzymes [ 27 , 28 , 29 ]. Nrf2 binding with the antioxidant responsive element (ARE) leads to the transcriptional activation of downstream genes such as NAD(P)H: quinone oxidoreductase (NQO1), glutathione-S-transferase (GST), and hemeoxygenase-1 (HO-1) [ 27 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigations of the protective effects of Keap1/Nrf2 signaling that focus on specific tissues or organs are of great interest. Such studies have traditionally focused on tissues with detoxification functions such as the liver [ 6 , 7 ] but have also expanded to diverse tissues, including the kidney [ 8 , 9 ], skin [ 10 ], lung [ 11 ], colon [ 12 ], heart [ 13 ], nervous system [ 14 ], adipose tissue [ 15 ], pancreas [ 16 ] and thyroid [ 17 , 18 ], as evidenced by the respective tissue/organ-specific studies that are outlined below and comprise the majority of studies in the present Special Issue. Lastly, research on Nrf2 has expanded to encompass not only basic but also translational and clinical studies.…”
mentioning
confidence: 99%
“…Reactive oxygen species are produced by mitochondria during activity in various muscle tissues, including the heart, where the role of Keap1/Nrf2 signaling in ischemia–reperfusion injury has been well established [ 32 ]. In a study using rats, Younis et al extend these observations by showing that geraniol, an Nrf2-activating phytochemical, has protective effects on oxidative, inflammatory and apoptotic alterations in isoproterenol-induced myocardial infarction [ 13 ]. Similar to the aforementioned studies, involvement of Keap1/Nrf2 signaling is inferred indirectly by the induction of antioxidant and cytoprotective genes.…”
mentioning
confidence: 99%